EVALUASI PERESEPAN OBAT ANTIKOLESTEROL PADA PASIEN GERIATRI PERIODE JANUARI-FEBRUARI 2023 - Heny Puspasari; Deny Kusuma; Rayna Iza Azyra (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Hypercholesterolemia is a disease that is a leading cause of total mortality in Indonesia as well as worldwide. The prevalence of hypercholesterolemia is approximately 45% globally, around 30% in Southeast Asia, 35% in Indonesia, and 37.7% in West Kalimantan. In the management of hypercholesterolemia, evaluation and prescription patterns are crucial to reduce the risk of errors in prescribing anti-cholesterol drugs. The aim of this study was to evaluate the prescription of anti-cholesterol drugs in geriatric patients at Bhayangkara Anton Soedjarwo Hospital, Pontianak, during the period of January–February 2023. This study is a quantitative descriptive study using prescription data from outpatient geriatric patients receiving anti-hypercholesterolemia medication. The sample size was determined using the Lemeshow formula, resulting in 100 respondents selected through simple random sampling. The results showed that hypercholesterolemia patients were most prevalent in the 61–65-year age group, accounting for 22%, with females comprising 56%. The most frequently used anti-cholesterol drug was Atorvastatin (78%), with a dose of 20 mg, administered once daily in 98% of cases, and the most common comorbidity was heart disease (49%). The use of anti-cholesterol drugs was considered rational if it met the criteria of correct diagnosis, correct patient, correct disease indication, correct drug selection, and correct dosage, achieving a rationality rate of 100%. The study findings indicate that the most frequently prescribed anti-hypercholesterolemia drug was Atorvastatin, with rational prescribing practices observed in hypercholesterolemia patients.